2022
DOI: 10.7554/elife.81282
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical contributions to cognitive task activity

Abstract: Thalamocortical interaction is a ubiquitous functional motif in the mammalian brain. Previously (Hwang et al., 2021), we reported that lesions to network hubs in the human thalamus are associated with multi-domain behavioral impairments in language, memory, and executive functions. Here we show how task-evoked thalamic activity are organized to support these broad cognitive abilities. We analyzed functional MRI data from human subjects that performed 127 tasks encompassing a broad range of cognitive representa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Through this converging input, thalamic neurons extract a summary signal from multiple converging cortical inputs, encoding a low-dimensional, compressed representation abstracted from the high-dimensional inputs. This observation is further consistent with our prior fMRI studies, where we found that relative to the cortex, the thalamus encodes low-dimensional structures of cognitive activity (Hwang et al, 2022), and that thalamic subregions showing the strongest context coding also exhibit converging connectivity (hub-like connectivity) with multiple frontoparietal structures (Hwang et al, 2017, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Through this converging input, thalamic neurons extract a summary signal from multiple converging cortical inputs, encoding a low-dimensional, compressed representation abstracted from the high-dimensional inputs. This observation is further consistent with our prior fMRI studies, where we found that relative to the cortex, the thalamus encodes low-dimensional structures of cognitive activity (Hwang et al, 2022), and that thalamic subregions showing the strongest context coding also exhibit converging connectivity (hub-like connectivity) with multiple frontoparietal structures (Hwang et al, 2017, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the anterior, medial, and posterior thalamus exhibit strong converging connectivity with multiple frontal-parietal systems that have been implicated in control-related functions (Hwang et al, 2017). The behavioral significance of this thalamocortical connectivity profile is further affirmed by recent functional neuroimaging studies (Chen et al, 2023;Hwang et al, 2022) and lesion evidence (Hwang et al, 2021(Hwang et al, , 2022. However, it remains unclear how thalamocortical connectivity supports hierarchical cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“…The thalamocortical radiations are essential for transmitting information and help regulate cortical arousal and consciousness. Moreover, through their connections with different cortical regions, they are involved in higher-order cognitive functions [82]. Our work reconstructed thalamic radiations using the whole thalamus as a starting region and the cortical targets as the end regions.…”
Section: Resultsmentioning
confidence: 99%
“…In future work it would be of interest to compare different mechanisms by which the cerebellum may realise context-dependent processing; for example, a recent study has suggested that dendritic gating via cerebellar interneurons may perform this role 72 . Moreover, recent observations suggest that the cerebellar-driven thalamus enables context-dependent responses in the cortex for movement initiation 51,56 and cognitive tasks 73 . Indeed, our work suggests that fast context-switching is easier to incorporate in the relatively simple, divergent and rapidly learnable feedforward architecture of the cerebellum compared to the highly intricate cortical RNNs with weak plasticity.…”
Section: Discussionmentioning
confidence: 99%